gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Reconstructing the volcanic history of the Ulukışla Caldera: A collapse structure within the Hasandağ Volcanic Complex, Central Anatolia (Turkey) - Rengin Özsoy; Ivan Sunyé-Puchol; Xavier Bolós; Efe Akkaş; Antonio Costa; Lorenzo Tavazzani; Daniel P. Miggins; Manuela Nazzari; Olivier Bachmann; Piergiorgio Scarlato; Silvio Mollo (Journal of Volcanology and Geothermal Research, 2025)

Reconstructing the Belbaşhanı Pumice Plinian eruption, Hasandağ Volcano, Turkey - Rengin Özsoy; Ivan Sunyé-Puchol; Dario Pedrazzi; Efe Akkaş; Antonio Costa; Silvia Massaro; Lorenzo Tavazzani; Manuela Nazzari; Olivier Bachmann; Piergiorgio Scarlato; Daniel P. Miggins; Simge Kaya; et al. (Bulletin of Volcanology, 2024)
Hasandağ volcano (Central Anatolia, Turkey) has recently underwent an increase in local seismicity and fumarolic activity since 2013. In the past, this volcano has produced multiple large explosive eruptions during the last million years. The Belbaşhanı Pumice is the product of a sub-Plinian to Plinian eruption dated at ~ 417 ± 20.5 ka ( 40 Ar/ 39 Ar). Here, we present a complete volcanological study including stratigraphy, glass chemistry, pumice morphology, geochronology, and eruption source parameters with the associated uncertainties, to characterize the Belbaşhanı Pumice eruption. The eruption involved a column of 18–29 km in height, with the main dispersal axis towards the northeast. A pumice layer up to ~ 17-m-thick accumulated in proximal deposits along the Belbaşhanı path, and up to 2-m-thick in medial-distal areas (~ 18 km northeast from the vent). The high and tubular vesicularity of the pumice clasts indicates that the Belbaşhanı eruption was predominantly magmatic. The bulk volume of the Belbaşhanı Pumice fallout deposit has been estimated as 0.5 and 8 km 3 (with ~ 2 km 3 being the mean value), which corresponds to Volcanic Explosivity Index (VEI) of at least 4 and up to 6. Both isopach and isopleth maps indicate that the volcanic vent may have been located at the intersection of the Tuz Gölü fault and Ulukışla caldera, within the Hasandağ volcanic complex. The glass composition of Belbaşhanı Pumice confirms that the eruption belongs to the Hasandağ magmatic system. The reconstruction of the Belbaşhanı Pumice eruption represents an essential baseline in providing volcanological constraints for further investigations of tephra fallout hazard assessment in Central Anatolia, especially considering that a new Plinian eruption cannot be ruled out at Hasandağ volcano in the future. The chemical and geochronological datasets presented here could aid in refining tephrochronological correlations, with the goal of synchronizing paleoenvironmental and paleoclimatic records alongside archaeological sites.

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Effect of undercooling on clinopyroxene crystallization in a high K basalt: Implications for magma dynamics at Stromboli volcano - F. Colle; M. Masotta; S. Costa; S. Mollo; P. Landi; A. Pontesilli; S. Peres; L. Mancini (Lithos, 2023)

The efficacy of high frequency petrological investigation at open-conduit volcanoes: The case of May 11 2019 explosions at southwestern and northeastern craters of Stromboli - A. Pontesilli; E. Del Bello; P. Scarlato; S. Mollo; B. Ellis; D. Andronico; J. Taddeucci; M. Nazzari (Lithos, 2023)

Plagioclase crystal size distribution parameterization: A tool for tracking magma dynamics at Stromboli - B. Schiavon; S. Mollo; A. Pontesilli; E. Del Bello; M. Nazzari; P. Scarlato (Lithos, 2023)

A review of plagioclase growth rate and compositional evolution in mafic alkaline magmas: Guidelines for thermometry, hygrometry, and timescales of magma dynamics at Stromboli and Mt. Etna - P. Moschini; S. Mollo; A. Pontesilli; M. Nazzari; C.M. Petrone; S. Fanara; A. Vona; M. Gaeta; C. Romano; P. Scarlato (Earth-Science Reviews, 2023)

Sensitivity Analysis of Single Beat Left Ventricular Elastance Estimation by Chen Method - A. Di Molfetta; G. Ferrari; V. Cusimano; G. Di Ruzza; P. Mollo; D. Boncompagni; M. Cesario; C. Volponi; M. Massetti; M. Menichelli (Cardiovascular Engineering and Technology, 2022)

Experimental constraints on the origin of pahoehoe “cicirara” lavas at Mt. Etna Volcano (Sicily, Italy) - F. Vetere; S. Mollo; P. P. Giacomoni; G. Iezzi; M. Coltorti; C. Ferlito; F. Holtz; D. Perugini; P. Scarlato (Bulletin of Volcanology, 2015)

The role of natural solidification paths on REE partitioning between clinopyroxene and melt - P. Scarlato; S. Mollo; J. D. Blundy; G. Iezzi; M. Tiepolo (Bulletin of Volcanology, 2014)

The partitioning of trace elements between clinopyroxene and trachybasaltic melt during rapid cooling and crystal growth - S. Mollo; J. D. Blundy; G. Iezzi; P. Scarlato; A. Langone (Contributions to Mineralogy and Petrology, 2013)